The future scribe: Learning to write the world - Lindberg, Ylva; Öberg, Lena-Maria (Frontiers in Education, 2023)
This study takes its point of departure in academic scholarship that points to how programming – reading and writing code – is the literacy of the future, in other words, non-specialized competence that should be acquired in education in parity with traditional reading and writing skills. The goal is to shed light on how programming can be orchestrated in education to break with the outworn dichotomy between the ‘two cultures’ that C. P. Snow formulated as a gap between, on the one hand, natural sciences, mathematics and technology, and, on the other hand, the humanities and social sciences. The study is situated in a Swedish compulsory school context and comprises of three data sets constructed in the following mediating instances of education: 1) policy documents and curricula, 2) daily press, and 3) academic research. In this stage, the analysis is delimited to the first instance. The results show that Swedish curricula are framing programming as specialized knowledge within technology and mathematics, rather than allowing it to be a dimension of several subjects, such as the humanities and social sciences. These findings will advance knowledge about the conditions for implementing reading and writing code as digital literacy in education.